Quality seed for tree planting: Supporting more effective agroforestry and forest landscape restoration by learning from crop Integrated Seed System Development - Lillesø, Jens-Peter B.; Dawson, Ian K.; Graudal, Lars; Jamnadass, Ramni H. (World Agroforestry Centre, 2021)
Tree planting in agroforestry and wider restoration work often relies on poor quality tree seed. However, the high demand for tree seed from large global restoration commitments and a new focus on accountability provide the opportunity for change. The goal should be to release or realize the potential of rural organizations, small-scale private nurseries and local communities to effectively participate in tree seed supply systems. This can be done through a process of integrating formal and informal approaches, and by supporting the development of informal suppliers into a well-functioning commercial sector. In this brief we outline the current status of tree seed supply in the tropics and compare it with the crop sector, to understand what can be learnt from the latter, and where tree seed supply provides unique challenges. We discuss areas where policy to support tree seed supply can be improved.